COMMON CAUSES OF TRAFFIC ACCIDENTS AND HOW TO PREVENT THEM (Лучшие интеллектуальные исследования, 2025)
ABSTRACT: Traffic accidents are a major concern worldwide, leading to injuries, fatalities, and property damage. This article explores the most common causes of traffic accidents, such as speeding, distracted driving, driving under the influence, and poor road conditions. It also highlights practical prevention strategies, including stricter law enforcement, public education, improved road infrastructure, and the use of modern technologies. Understanding these factors is crucial for reducing accidents and promoting safer roads for all users.